(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Antibiotic resistance among pyogenic bacteria has been gradually increasing Using antibiotics without proper determination of susceptibility and resistant pattern may lead to antibiotic abuse and ultimately antibiotic resistance. It is important to have knowledge about susceptibility and resistant pattern of organisms isolated from pus to choose the correct treatment regimen. Objective: To determine the antibiotic susceptibility & resistant pattern of pyogenic bacteria isolated from pyogenic infection. Methods: A cross sectional study was carried out at the Department of Microbiology, Dhaka National Medical College & Hospital from January 2021 to July 2021. A total 200 samples were taken from various clinical specimen containing pus. Samples from cases of Urethritis, Cervicitis, Meningitis, UTI or other Sexually transmitted infection were excluded from this study. Purulent conjunctival swab, ear swab, pus from wound, (surgical and accidental) abscess, were firstly tested by gram staining. Then cultured on Mac Conkey agar media & Blood agar media as well as Chocolate agar media if necessary. Then media were incubated at 37ºc for 24-48 hours. Colonies grown on to media were further tested for coagulase test, biochemical reaction(oxidase test, and inoculated into soft agar media as TSI,) At last susceptibility and resistant pattern were tested on to Muller-Hinton agar media. Results: A total 200 samples were taken from various clinical specimen containing pus Staphylococcus aureus is the predominant among gram positive organisms. Among gram negative bacteria, Klebsiella pneumonia was the predominant organism. Staphylococcus aureus exhibit sensitivity to Vancomycin, Linezolid, Imipenem, Amikacin, Fusidic acid & Amoxicillin -Clavalinic acid combination. Staphylococcus aureus showed highest sensitivity to Vancomycin & exhibit maximum resistant to Cefixime. Pseudomonas showed a very good sensitivity to Amikacin, Imipenem, Tazobactam & Gentamycin but resistant to Ceftazidime and Co-trimoxazole. Pseudomonas is highly sensitive to Amikacin & highly resistant to Ceftazidime. Antimicrobial susceptibility of E.coli showed a very good sensitivity to Imipenem, Amikacin, Amoxiclav, Ceftriaxone & Ciprofloxacin but resistant to Cefixime, Cephradine, Ceftazidime & Cefuroxime. E.coli exhibit maximum sensitivity to Imipenem followed by Amikacin & showed maximum resistant to Cefixime. Conclusion: This study showed that most common Pyogenic bacteria isolated from various clinical specimen are Staphylococcus aureus, Klebsiella spp, Pseudomonas spp, E. coli & Streptococcus pyogenes. Different bacteria differ in response to different antibiotic therapy. Based on this study it may be concluded that testing of sensitivity and resistant before starting antibiotic treatment is very important to prevent emergence of drug resistance bacterial strain. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 28-33